Snow Leopards - Grack, Rachel, (Rachel A. Koestler-Grack), 1973-; Downs, Kieran (Minneapolis, Minnesota : Bellwether Media, 2023)
"Relevant images match informative text in this introduction to snow leopards. Intended for students in kindergarten through third grade"--
Includes bibliographical references and index.
Keywords: Snow leopard -- Juvenile literature; Snow leopard -- Conservation -- Juvenile literature